Genome-wide identification, characterization and evolutionary analysis of the pyrroline-5-carboxylate synthetase (P5CS), succinic semialdehyde dehydrogenase (SSADH), and dehydrin (DHN) genes in Solanum lycopersicum under drought stress - Amaal Maghraby; Mohamed Alzalaty (BMC Plant Biology)
Abstract Background The pyrroline-5-carboxylate synthetase (P5CS), succinic semialdehyde dehydrogenase (SSADH), and dehydrin (DHN) genes are involved in plant drought response. Methods A comprehensive bioinformatics approach was applied, including phylogenetic, structural, evolutionary, and functional analyses, as well as promoter, subcellular localization, and gene ontology assessments. Results This is the first study to identify the P5CS, SSADH and DHN genes in Solanum lycopersicum via genome-wide analysis under drought stress. We identify 2 P5CS, 18 SSADH and 16 DHN genes in S. lycopersicum. The chromosomal distribution showed that P5CS genes were located on chromosomes 6 and 8, SSADH genes on chromosomes 1, 2, 3, 5, 6, 7, 8, 9, and 12, and DHN genes on chromosomes 1, 2, 3, 4, 5, 6, 7, 8, 9,10, and 12. The Ka/Ks ratios indicated that the P5CS, SSADH and DHN genes were influenced primarily by negative selection, which indicated that the P5CS, SSADH and DHN genes received strong environmental pressure during evolution. The duplication time of the P5CS paralogous gene pairs was approximately 40.030 Mya. The duplication time of the SSADH paralogous gene pair ranged from approximately 31.495 to 45.966 Mya. The duplication time of the DHN paralogous gene pairs ranged from approximately 1.645 to 102.128 Mya. Synteny analysis of the P5CS, SSADH and DHN genes revealed collinearity orthologous relationships in Solanum tuberosum and Arabidopsis thaliana but no orthologs of the P5CS, SSADH and DHN genes with Oryza sativa. In addition, collinearity analysis revealed that 1 orthologous P5CS genes, 20 orthologous SSADH genes and 5 orthologous DHN genes were paired with those in S. tuberosum. Additionally, collinearity analysis revealed that 15 orthologous SSADH genes, 5 orthologous DHN gene and no orthologous P5CS genes, were paired with those in A. thaliana. The qRT–PCR results indicated that P5CS and DHN were upregulated, with fold changes of 2.39 and 1.23, respectively, whereas SSADH expression decreased with a fold change of 0.73. Conclusions Our results provide comprehensive insights into the P5CS, SSADH, and DHN genes, including their protein structures and predicted interaction features. These findings offer valuable targets for tomato breeding programs aimed at developing stress-tolerant varieties under changing climate conditions.